2019
DOI: 10.1080/2090598x.2019.1651016
|View full text |Cite
|
Sign up to set email alerts
|

Literature review and case report of post-circumcision keloid management

Abstract: Keloid following circumcision has been described in the literature despite the rarity of its occurrence in penile skin. In this paper, we review the literature and report the successful management of post-circumcision keloid scarring in a 2-year-old boy. After circumcision a 2-year-old boy of African origin developed keloid scarring at the circumcision site. This was treated with three intralesional injections of triamcinolone acetate over 3 months, followed by surgical excision. There was no recurrence at 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Keloid formation is most common in the ear lobule. However, it can be found in the upper chest, shoulders, upper back, head, and neck and rarely in the penis [7].…”
Section: Discussionmentioning
confidence: 99%
“…Keloid formation is most common in the ear lobule. However, it can be found in the upper chest, shoulders, upper back, head, and neck and rarely in the penis [7].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the most popular means of treating penile KS after circumcision has been excision followed by corticosteroid intralesional injections [3,8]. Penile KS post-circumcision have been reported in twenty different cases ranging from 1993 to 2020 with twelve of the patients receiving excision followed by intralesional steroid injections [4,24]. Only one case demonstrated recurrence; subsequently the patient underwent repeat excision with triamcinolone intralesional injections with no recurrence.…”
Section: Proposed Treatments For Penile Circumcision Keloidmentioning
confidence: 99%
“…Four patients underwent intralesional triamcinolone injections only and one with excision only, all without recurrence [18,21,24]. There are also three studies that showed no demonstrated recurrence when intralesional injections were administered prior to surgical excision of the KS [4,22]. Of note, 20 percent of the study population had a prior history of KS formation.…”
Section: Proposed Treatments For Penile Circumcision Keloidmentioning
confidence: 99%
See 1 more Smart Citation